Framing innocents: the wrongly convicted as victims of state harm - Westervelt, Saundra Davis (Crime, law and social change, 2010)
We adapt the victimology of ‘state harms’ framework outlined by Kauzlarich et al. (Critical Criminology, 10(3), 173-194, 2001) to understand the post-exoneration experiences of 18 death row exonerees. Kauzlarich et al. develop six points of commonality shared by most victims of state crime. Application of this framework to death row exonerees highlights the role the state plays in creating and exacerbating the harms they suffer. This analysis also lays a foundation for further theoretical inquiry into the wrongful conviction of the innocent as a form of state crime.